Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which ordered pair is a solution to the equation [tex]\( y - 3 = 5(x - 2) \)[/tex], let's substitute each pair into the equation and see if it holds true.
### First Pair: [tex]\((2, 3)\)[/tex]
1. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 3\)[/tex] into [tex]\( y - 3 = 5(x - 2) \)[/tex]:
[tex]\[ 3 - 3 = 5(2 - 2) \][/tex]
2. Simplify the left side and right side of the equation:
[tex]\[ 0 = 5(0) \][/tex]
[tex]\[ 0 = 0 \][/tex]
Since the equation holds true, the ordered pair [tex]\((2, 3)\)[/tex] satisfies the equation.
### Second Pair: [tex]\((3, 2)\)[/tex]
1. Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = 2\)[/tex] into [tex]\( y - 3 = 5(x - 2) \)[/tex]:
[tex]\[ 2 - 3 = 5(3 - 2) \][/tex]
2. Simplify the left side and right side of the equation:
[tex]\[ -1 = 5(1) \][/tex]
[tex]\[ -1 = 5 \][/tex]
Since the equation does not hold true, the ordered pair [tex]\((3, 2)\)[/tex] does not satisfy the equation.
### Conclusion
From the above analysis, we can see that only [tex]\((2, 3)\)[/tex] satisfies the given equation.
Thus, the correct answer is:
(A) Only [tex]\((2, 3)\)[/tex]
### First Pair: [tex]\((2, 3)\)[/tex]
1. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 3\)[/tex] into [tex]\( y - 3 = 5(x - 2) \)[/tex]:
[tex]\[ 3 - 3 = 5(2 - 2) \][/tex]
2. Simplify the left side and right side of the equation:
[tex]\[ 0 = 5(0) \][/tex]
[tex]\[ 0 = 0 \][/tex]
Since the equation holds true, the ordered pair [tex]\((2, 3)\)[/tex] satisfies the equation.
### Second Pair: [tex]\((3, 2)\)[/tex]
1. Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = 2\)[/tex] into [tex]\( y - 3 = 5(x - 2) \)[/tex]:
[tex]\[ 2 - 3 = 5(3 - 2) \][/tex]
2. Simplify the left side and right side of the equation:
[tex]\[ -1 = 5(1) \][/tex]
[tex]\[ -1 = 5 \][/tex]
Since the equation does not hold true, the ordered pair [tex]\((3, 2)\)[/tex] does not satisfy the equation.
### Conclusion
From the above analysis, we can see that only [tex]\((2, 3)\)[/tex] satisfies the given equation.
Thus, the correct answer is:
(A) Only [tex]\((2, 3)\)[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.